2021
DOI: 10.1002/qj.4148
|View full text |Cite
|
Sign up to set email alerts
|

Recurvature and movement processes of tropical cyclones over the Bay of Bengal

Abstract: Active bimodal tropical cyclones (TCs) are embedded in nonuniform flows over the Bay of Bengal (BoB). More than half of the TCs that occurred from 1990 to 2019 recurved from their original path due to the influence of 500–300 hPa steering flows. Premonsoon TCs have a tendency to turn right and make landfall on the right‐side coastal areas of the BoB. On the other hand, most of the TCs that occurred in the postmonsoon season crossed the left coast or east coast of India, despite being left or right from their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 78 publications
1
2
0
Order By: Relevance
“…A large number of storms is also observed along the eastern coast of Bangladesh. This landfall pattern corresponds to previous observations that the cyclones making landfall on the Bangladesh coastline tend to move north-eastward (Ali, 1996;Akter and Tsuboki, 2021;Mondal et al, 2021).…”
Section: Synthetic Cyclone Ensembles Statisticssupporting
confidence: 90%
“…A large number of storms is also observed along the eastern coast of Bangladesh. This landfall pattern corresponds to previous observations that the cyclones making landfall on the Bangladesh coastline tend to move north-eastward (Ali, 1996;Akter and Tsuboki, 2021;Mondal et al, 2021).…”
Section: Synthetic Cyclone Ensembles Statisticssupporting
confidence: 90%
“…This is so that the storm's track and intensity are affected by how the storm is being pushed by the mid-level winds. Because of the influence of 500-300 hPa steering flows, more than half of the TCs over BoB that occurred from 1990 to 2019 recurved from their original path (Akter and Tsuboki 2021). It is found that interaction between westerlies and easterlies at east Indian coastal belts (5-6 m s −1 ) at mid-level during the pre-monsoon season over the BoB basin in the recent decade (figure 5(a)) created a barrier for storms headed towards BGD and MMR while allowing them to take a diversion towards the eastern Indian coastal landmass.…”
Section: Windmentioning
confidence: 99%
“…Between 2013 and 2017, excluding 2014, four Category 1 cyclones affected the coastal region of Bangladesh: Mahasen in 2013, Komen in 2015, Roanu in 2016, and Mora in 2017; the number of deaths associated with each was less than 50. Studies were undertaken to understand the physical characteristics of these cyclones, their impacts, and the evacuation behaviour of coastal residents (Saha and James, 2017; Akter and Tsuboki, 2021; Rafa, Jubayer, and Uddin, 2021). From a social vulnerability and people‐response perspective, the reasons for not moving to the cyclone shelters and non‐compliance with warning signals during these tropical cyclones were similarly noted as before (Ibrahim, Rahman, and Rezwana, 2019; Chakma and Hokugo, 2020).…”
Section: Assessing Cyclone Hazard Exposure and Vulnerability In Bangl...mentioning
confidence: 99%